2015
DOI: 10.1021/acs.jpclett.5b00149
|View full text |Cite
|
Sign up to set email alerts
|

Switching Oxygen Reduction Pathway by Exfoliating Graphitic Carbon Nitride for Enhanced Photocatalytic Phenol Degradation

Abstract: The selectivity of molecular oxygen activation on the exfoliated graphitic carbon nitride (g-C 3 N 4 ) and its influence on the photocatalytic phenol degradation process were demonstrated. Compared with bulk g-C 3 N 4 , the exfoliated nanosheet yielded a 3-fold enhancement in photocatalytic phenol degradation. ROS trapping experiments demonstrated that although the direct hole oxidation was mainly responsible for phenol photodegradation on both g-C 3 N 4 catalysts, molecular oxygen activation processes on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 30 publications
(47 reference statements)
3
74
0
1
Order By: Relevance
“…Noticeably, the exfoliation process caused an obvious blue shift to 415 nm, accompanying by the bandgap broadening to 2.99 eV, which is consistent with literatures91011. It was reported that the conduction band (CB) and valence band (VB) edges shifted in opposite direction after exfoliation due to the quantum effect45. Fortunately, the molecular grafting of remarkably altered the electronic structure so that the absorption edge onset of CNX is extended to ~600 nm1418.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Noticeably, the exfoliation process caused an obvious blue shift to 415 nm, accompanying by the bandgap broadening to 2.99 eV, which is consistent with literatures91011. It was reported that the conduction band (CB) and valence band (VB) edges shifted in opposite direction after exfoliation due to the quantum effect45. Fortunately, the molecular grafting of remarkably altered the electronic structure so that the absorption edge onset of CNX is extended to ~600 nm1418.…”
Section: Resultssupporting
confidence: 88%
“…The well-contacted RGO acted as an electron reservoir and transferred abundant photogenerated electrons to O 2 , favoring a two-electron process to H 2 O 2 45. It was found that the degradation rate in the presence of catalase was similar to that of t -BuOH.…”
Section: Resultsmentioning
confidence: 93%
“…Since the photogenerated holes in the valance band of g-C 3 N 4 (E VB = +1.40 V, vs. NHE) are incapable of oxidizing hydroxyl groups into • OH radicals (E ( • OH/OH − ) = +1.99 V, vs. NHE) due to the more negative valance band potential [42], it is believed that the observed • OH radicals were generated from the • O 2 − radicals by photochemical reaction. Time-dependent ESR signals were also measured under the same conditions, where the intensity of the ESR signal could imply the concentration of ROS generated in each catalyst suspension.…”
Section: Photocatalytic Mechanism For G-c 3 N 4 /Cds Compositesmentioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ), as a metal-free polymeric semiconductor, has shown huge potential in the field of photocatalytic H 2 evolution [1][2][3], CO 2 reduction [4,5], contamination elimination [6,7], and H 2 O 2 synthesis [8][9][10]. With an optical band gap of 2.70 eV, g-C 3 N 4 has shown a response to visible light up to 460 nm.…”
Section: Introductionmentioning
confidence: 99%